Legal Implications of Autonomous Warships under UNCLOS: Navigating Definitional Gaps in International Maritime Law - Afiat Yudhistira; Davina Oktivana (Lex Publica, 2025)
Rapid technological advancements have outpaced legal frameworks in regulating autonomous warships, as United Nations Convention on the Law of the Sea (UNCLOS) human-centered definition fails to accommodate crewless or semi-autonomous vessels in modern naval operations. This study examines the legal implications of this definitional gap and explores how international law might evolve to address the governance of autonomous warships. Key issues include sovereignty, accountability, and compliance with existing maritime and wartime legal norms, such as whether a fully autonomous vessel can qualify as a warship under UNCLOS and what responsibilities states bear for their actions in conflict scenarios. Using a normative legal research design with doctrinal and conceptual approaches, the study analyzes UNCLOS, COLREGs, and SOLAS, employing deductive and analogical reasoning to compare autonomous vessels with technologies like remotely piloted UAVs. Autonomous warships do not fully qualify as warships under UNCLOS due to the absence of human command and crew, leading to ambiguities in liability, navigation compliance, cybersecurity risks, and humanitarian duties. However, remote operation and flag state discretion may allow classification, highlighting gaps in existing frameworks.